Pre and Post Lockdown Impacts On Sectors Indices with Reference to Bombay Stock Exchange - Dr. Prateek Kumar Bansal (International Journal of Modern Agriculture, 2021)
Lockdown was the primary measure taken by various countries to prevent spread of Covid-19 pandemic rapidly. It had also effect on global economy. Lockdown was announced in India on 24th March 2020 and implemented on 25th march 2020. This study is an attempt to analyses the impact of Covid-19 pandemic on stock indices in India. Due to lockdown restrictions was imposed on all commercial activities and the people have to remain in their houses which caused several kind of financial problem in market. In this study data of stock indices from 24th January to 24th March 2020 and from 25th March to 31st May 2020 have been taken as the indicator of Pre and Post lockdown period. For the purpose of analysis Relative Strength Index has been calculated for the market data of indices and Paired Sample t-test has been applied as statistical tool to measure significance level. Our results indicated that there is significant impact of lockdown on stock indices. This study is also useful to understand the effect of emergencies on stock indices.